PENGARUH PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN PUMA STORE CABANG BANDUNG INDAH PLAZA - Dian Candra Fatihah (EKBIS (Ekonomi & Bisnis), 2020)
ABSTRACT This research aimed to determine The Effect of Compensation on The Performance of Emplyoyess Puma Store Bandung Indah Plaza Brach. The method used in this research is quantitative method. The data collection technique was carried out by means of literature study, interviews and questionnaries. The data analysis techniques used are descriptive analysis, validity test, realibity test, normality test, correlation coeffiesient, determination coefficient, simple linier regression analysis, and hypothesis testing. From the research that has been done, the correlation coefficient is 0,816 which menas that it is positibely related to a very strong level of relationship, and the determination coefficient is 66,6% which shows the magnitude of the effect of compensation on employee performance and the remaininng 33,4% in influeced by other which were not examined in this research. The linier regression equation Y = a + bX = 7,740 + 0,634 X, which menas that every 1 increase i compensation, the performance will increase by 0,634. From the test results obtained 7,473> 2,048 (tcount > ttable), then Ho is rejected adn Ha is accepted, which means that there is a significant influence between compensation on employee performance. As for the suggestions given among other, the company should pay more attention to the work bonuses given, should conduct more effective training for employee, and open up the aspects of career paths for employess. Keyword : Compensation, Performance.